Edukasi Pencegahan Penyakit Demam Berdarah Dengue (DBD) melalui Kelompok “Sobat Lawan Jentik” di SMP Negeri 7 Tasikmalaya - Setiyono, Andik; Maulidi Tanjung, Muhamad Fajar (Universitas Pahlawan Tuanku Tambusai, 2025)
Dengue hemorrhagic fever (DHF) continues to be a significant public health concern worldwide, including in Indonesia. The highest incidence of fatal cases due to dengue fever is observed among school-aged children. Consequently, the eradication of mosquito nests (PSN) is imperative to prevent dengue fever. The efficacy of the prevention program is attributable to its success in empowering the community, including educational institutions, through the establishment of jumantik cadres. The objective of this initiative is to enhance the knowledge and attitudes of jumantik cadres, specifically the